A novel mechanism for A-to-I RNA-edited CYP1A1 in promoting cancer progression in NSCLC - Zhipeng Wang; Yan Wu; Ziqi Ding; Xinru Xiao; Yanhua Huang; Zhiguang Liu; Qian Zhang (Cellular & Molecular Biology Letters)
Abstract Background Lung cancer is the most frequently diagnosed malignancy and the leading cause of cancer-related mortality worldwide. Similar to other solid tumors, the development of non-small cell lung cancer (NSCLC) is believed to be a multistep process involving the accumulation of genetic and epigenetic alterations. A-to-I RNA editing is a widespread posttranscriptional epigenetic modification that confers specific nucleotide changes in selected RNA transcripts and plays a critical role in the pathogenesis of many human cancers. However, the mechanisms underlying A-to-I RNA editing that act as a potential driver in the pathogenesis of NSCLC progression remain incompletely elucidated. Methods Sanger sequencing was performed to validate the CYP1A1_I462V RNA editing event in NSCLC patients. In vitro and in vivo experiments were used to assess the effects of an ADAR1-regulated CYP1A1 and its editing on NSCLC cell growth and metastasis. The crosstalk between CYP1A1_I462V RNA editing and PI3K-AKT signaling was analyzed using RNA sequencing and molecular methods. The functional role of CYP1A1_I462V in the response to oxidative stress was verified through proteomics analysis, co-IP assay, and immunofluorescence assay. Results Sanger sequencing analysis identified an increased A-to-I RNA editing ratio of CYP1A1 in NSCLC specimens. This specific RNA editing, regulated by ADAR1, resulted in gain-of-function phenotypes characterized by enhanced tumor progression and more aggressive behavior. The edited form induced the expression of heme oxygenase-1 (HO-1) via PI3K/Akt-dependent activation compared with the wild-type CYP1A1, which led to an enhanced interaction with CYP1A1, thereby promoting the translocation of abundant HO-1 into the nucleus to resist oxidant stress in NSCLC cells. Conclusions Our findings highlight that the I462V A-to-I RNA editing event of CYP1A1 drives pulmonary carcinogenesis through inhibiting oxidative stress and suggest that the CYP1A1-HO-1-PI3K/Akt axis may be a potential therapeutic target for NSCLC. Graphical Abstract